Pedagogical competence of secondary teachers’: Views of teacher educators - Λιακοπούλου, Μαρία (Education Sciences, 2024)
Despite the recognized contribution of teacher education to their effectiveness, inadequacies and weaknesses of teacher preparation curricula are highlighted. In particular, the pedagogical and didactic training of Secondary teachers is still a demand and not only for the Greek reality. As far as the Greek reality is concerned, since 1997 this issue has been raised at the level of educational policy (Law 2525). In this article it was deemed necessary to focus on the views of the teacher educators. The aim of the research was to record the views of teacher educators regarding the pedagogical and didactic training of their students, and in particular regarding the duration, organization and content that they believe this training should have. Specifically, 166 teacher educators participated in the survey and useful information emerged regarding the organization and content that they believe the pedagogical training of prospective teachers should have, as well as the obstacles that exist in consolidating the relevant practices and ‘politics’.